Analisis Kualitas Distribusi Air Menggunakan Metode Six Sigma DMAIC Pada PDAM Surya Sembada Kota Surabaya - Evi Maria Ulfah; Tuwanku Aria Auliandri (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
PDAM Surya Sembada Surabaya is a water supply company. This company distributes and supplies hygienic water to all residents in Surabaya. PDAM Surya Sembada Surabaya always tries to make customers satisfied with the provided services. Moreover, the company also tries to continue the improvements based on the management quality of ISO 9001: 2008. However, in the process of water distribution, some customers are still complaining due to the PDAM’s service, which indicates that not all the customers are satisfied. It is the duty of PDAM Surabaya to improve the quality services. This study focuses on providing the causes defects analysis of PDAM Surabaya Surya Sembada water distribution using the Six Sigma DMAIC. This study used descriptive qualitative approach with an emphasis on the question of how.  The results of the research proved that there are two defects in the water distribution change into CTQ; defect TDA (No Water) and IMR (stench muddy water). In 2015, performance of Surabaya PDAM Surya Sembada showed the DPMO value as 844 and the value of capability sigma as 4.64. Based on Pareto diagram, this study stated that the dominant defect is TDA. This study applied the basic cause effect diagram to show the defect cause problem and used FMEA as a recommendation for continuous improvement that is expected to achieve zero defects.